Research Progress on Influencing Factors and Intervention Measures of Post-traumatic Growth in Breast Cancer Patients - Fu, Xin; Sun, Jiao; Wang, Xiaoxu; Cui, Mingke; Zhang, Qiang (Frontiers in Public Health, 2022)
Breast cancer is the highest incidence of female malignant tumor in the world, and it shows an increasing trend year by year. It poses a great threat to women's life and health and has become a public health issue of global concern. Paying attention to the psychological response of cancer patients is of definite value in helping patients cope with the disease, return to society, reshape an active and healthy life, and improve their quality of life with cancer. In recent years, researchers have increasingly focused on the positive changes experienced by cancer patients from the perspective of positive psychology, namely post-traumatic growth. It is of great significance to explore individual and social resources to help patients grow and improve their survival ability and quality of life by paying attention to the potential resources and positive forces in the process of patients' fighting against diseases. This paper summarizes the influencing factors and intervention measures of post-traumatic growth of breast cancer patients, providing ideas and reference for clinical medical staff to carry out relevant intervention.